The Human Rights Commission and Child Labor: मानवाधिकार आयोग और बाल श्रमिकों के संदर्भ में - Mahavar, Dulhe Ram (RESEARCH HUB International Multidisciplinary Research Journal, 2024)
All member countries of the United Nations have acknowledged that children are the most valuable asset of a nation. A state that ensures the development of children and the well-being of mothers is considered a developed state. Therefore, representatives of all nations agreed that child human rights are a crucial issue that must be implemented as a necessity. India, being an established member of the United Nations, has incorporated fundamental rights into Part III of its Constitution to safeguard children's human rights. Articles 23 and 24 specifically address child labor. The responsibility for protecting human rights rests with the respective states. To fulfill this obligation, the Government of India established the National Human Rights Commission in 1993. Abstract in Hindi Language: संयुक्त राष्ट्र संघ के सभी सदस्य देषों ने यह स्वीकार किया कि बच्चे राष्ट्र की सबसे बहुमूल्य सम्पति है। जिस राज्य में बाल विकास एवं माताओं के विकास का ध्यान रखा जाता है वह राज्य विकसित राज्य की श्रेणी में आता है। इसलिए सभी राज्यों के प्रतिनिधियों ने इस पर अपनी सहमति दी की बाल मानवाधिकार एक मुख्य विषय है जिसे आवष्यक रूप में लागू करना चाहिए। भारत संयुक्त राष्ट्र संघ का स्थापित सदस्य है इसलिए उसने बच्चों के मानवाधिकारों को सुरक्षित रखने के लिए अपने संविधान में भाग-3 में मूल अधिकारों को जोडा गया जिसमें अनुच्छेद 23 व 24 विषेष रूप से बालश्रम से संबंधित है। मानवाधिकारों की सुरक्षा का दायित्व संबंधित राज्यों पर ही रखा गया इसी दायित्व को पूर्ण करने के लिए भारत सरकार के द्वारा 1993 में राष्ट्रीय मानवाधिकार आयोग की स्थापना की थी। Keywords: संयुक्त राष्ट्र संघ, बहुमूल्य, सम्पति, बाल विकास, विकसित, प्रतिनिधियों, मानवाधिकार, बालश्रम, मूल अधिकार